Histone deacetylase SIRT1 modulates neuronal differentiation by its nuclear translocation - Hisahara, Shin (National Academy of Sciences, 2008)
Neural precursor cells (NPCs) differentiate into neurons, astrocytes, and oligodendrocytes in response to intrinsic and extrinsic changes. Notch signals maintain undifferentiated NPCs, but the mechanisms underlying the neuronal differentiation are largely unknown. We show that SIRT1, an NAD(+)-dependent histone deacetylase, modulates neuronal differentiation. SIRT1 was found in the cytoplasm of embryonic and adult NPCs and was transiently localized in the nucleus in response to differentiation stimulus. SIRT1 started to translocate into the nucleus within 10 min after the transfer of NPCs into differentiation conditions, stayed in the nucleus, and then gradually retranslocated to the cytoplasm after several hours. The number of neurospheres that generated Tuj1(+) neurons was significantly decreased by pharmacological inhibitors of SIRT1, dominant-negative SIRT1 and SIRT1-siRNA, whereas overexpression of SIRT1, but not that of cytoplasm-localized mutant SIRT1, enhanced neuronal differentiation and decreased Hes1 expression. Expression of SIRT1-siRNA impaired neuronal differentiation and migration of NPCs into the cortical plate in the embryonic brain. Nuclear receptor corepressor (N-CoR), which has been reported to bind SIRT1, promoted neuronal differentiation and synergistically increased the number of Tuj1(+) neurons with SIRT1, and both bound the Hes1 promoter region in differentiating NPCs. Hes1 transactivation by Notch1 was inhibited by SIRT1 and/or N-CoR. Our study indicated that SIRT1 is a player of repressing Notch1-Hes1 signaling pathway, and its transient translocation into the nucleus may have a role in the differentiation of NPCs.